PENGARUH MODEL PROBLEM BASED LEARNING BERBANTUAN MEDIA GAMBAR BERSERI TERHADAP KETERAMPILAN MENULIS TEKS EKSPLANASI SISWA KELAS VIII SMP NEGERI 12 PADANG - Hizati, Amirah; R., Syahrul; Arief, Ermawati (Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2018)
The purpose of this study were (1) to describe the skills of wrting the text of the explanation of the students of class VIII SMP Negeri 12 Padang before using the serial image media aided problem based learning model, (2) to describe the skills of writing the text of the explanation of class VIII students of SMP Negeri 12 Padang after using problem based learning model serial image media, (3) to analyze the effect of serial image media aided problem based learning model to the writing skills skill of class VIII SMP Negeri 12 Padang. Based on data analysis, the use of serial image media-aided problem based learning model influences the writing skills skill of class VIII students of SMP Negeri 12 Padang. Â Kata kunci: pengaruh, problem based learningÂ¸ media gambar berseri, menulis teks eksplanasi